Economic impact of the Elecsys anti-Müllerian hormone Plus immunoassay for anti-Müllerian hormone testing as part of polycystic ovary syndrome assessment in the United Kingdom - Osvaldo Ulises Garay; Anna-Maria Olziersky; Joop Laven; Rebecca Mawson; Terhi Piltonen; Stephen Franks; Johanna Sillman (PLoS ONE, 2025)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder among women. Current international PCOS assessment and management guidelines recommend anti-Müllerian hormone (AMH) as an alternative to transvaginal ultrasound for assessing polycystic ovarian morphology, which is one of three criteria for diagnosing PCOS. This study assessed the economic impact of using the Elecsys® AMH Plus immunoassay (Roche Diagnostics International Ltd, Rotkreuz, Switzerland) for AMH testing in the United Kingdom health system to assess women with signs and symptoms of PCOS. A decision tree model estimated the costs and health outcomes of using the Elecsys AMH Plus immunoassay to determine polycystic ovarian morphology as part of PCOS assessment in a simulated cohort of women aged 25–45 years who were exposed to different diagnosis pathways. The comparator scenario was the standard of care, where transvaginal ultrasound was used for assessment. Base-case results indicated that the Elecsys AMH Plus immunoassay could lead to cost savings of £284,029 per year on the total cost of PCOS diagnosis (1.4% reduction vs. transvaginal ultrasound), in addition to savings on managing secondary comorbidities, such as type 2 diabetes and stroke care. Cost savings with the Elecsys AMH Plus immunoassay were observed in all scenarios versus using transvaginal ultrasound, including scenarios with various referral rates to specialists and dropout rates from the diagnosis pathway, and low adherence to lifestyle recommendations. With the known current delays in the United Kingdom for diagnosis of PCOS, implementing the Elecsys AMH Plus immunoassay for AMH testing may not only provide cost benefits, but also reduce waiting times for diagnosis and treatment, improving patient health outcomes.